2006
DOI: 10.1007/s10750-006-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Habitat Permanence Cues on Larval Abundance of Two Mosquito Species

Abstract: Fluctuations in mosquito populations can often be correlated with the level of rainfall in the short term, however, rainfall rarely corresponds to mosquito abundance in the long term. Here, we present results of a field based mesocosm experiment designed to test how variables associated with drought influence larval abundance of two species of mosquitoes. We used two water volumes (2 and 4 l) and two drought water concentrations (high and low). The two mosquito species present in these ponds, Ochlerotatus noto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Of the several variables and interactions that could affect the establishment of larval habitat, the influence of tank water volume seems to be important. Prior studies have found that water volume is a determining factor in the selection of a laying site and in the larval development of other mosquito species, such as Anopheles annulipes (Mokany and Mokany ). This parameter should be analyzed in more detail in forthcoming studies, but nevertheless, the results found in Girardot seem to indicate that Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the several variables and interactions that could affect the establishment of larval habitat, the influence of tank water volume seems to be important. Prior studies have found that water volume is a determining factor in the selection of a laying site and in the larval development of other mosquito species, such as Anopheles annulipes (Mokany and Mokany ). This parameter should be analyzed in more detail in forthcoming studies, but nevertheless, the results found in Girardot seem to indicate that Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The dissolved oxygen measured in the Girardot water tanks is not a limiting factor for Aedes sp. High concentrations of this gas may be negatively correlated with the presence of larvae (Mokany and Mokany , Tuten ). The similarity in the dissolved oxygen of the positive and negative containers is explained mainly by the location of all reservoirs under the same environmental conditions of temperature and altitude.…”
Section: Discussionmentioning
confidence: 99%
“…Water permanence in container habitats has been shown to highly influence mosquito abundance. The set up of plastic containers with small (2 L) and large (4 L) of water to mimic shallow and deep ponds resulted respectively in low and high prevalence of Anopheles annulipes larvae [60] . Such associations between mosquito abundance and water permanence have been also documented in dengue vectors.…”
Section: Discussionmentioning
confidence: 99%
“…quinquefasciatus egg rafts than that of the small volume pan. Mokany and Mokany (2006) noticed that Anopheles annulipes Walker, but not Ochlerotatus notoscriptus (ϭAedes notoscriptus), laid more eggs in 4 liters compared with 2 liters. They attributed this to differences in typical oviposition sites for the two species.…”
Section: Discussionmentioning
confidence: 99%